Diverse Changes of Circulating Fibroblast Growth Factor 21 Levels in Hepatitis B Virus-Related Diseases. Issue 1 (December 2017) - Wu, Liang; Pan, Qingchun; Wu, Guangyu; Qian, Lingling; Zhang, Jing; Zhang, Lei; Fang, Qichen; Zang, Guoqing; Wang, Yudong; Lau, George; Li, Huating; Jia, Weiping
Abstract Fibroblast growth factor 21 (FGF21), a stress-induced hormone in the liver, has been shown the protective functions in pathological conditions. The study investigated the association of circulating FGF21 with hepatitis B virus (HBV) infection and its related diseases. Serum FGF21 levels were measured in 33 acute hepatitis B (AHB), 75 chronic hepatitis B (CHB) and 66 CHB patients with advanced liver diseases including liver cirrhosis, acute-on-chronic liver failure (ALCF) and hepatocellular carcinoma (HCC) together with 200 age- and BMI-matched healthy controls. FGF21 levels were significantly increased in AHB patients and rapidly returned to normal levels after treatment. FGF21 levels reflected the degree of liver injury caused by AHB. However, serum FGF21 levels were decreased in CHB patients especially in those who developed cirrhosis and were associated with hepatic protein synthesis capacity. Serum FGF21 in CHB patients were increased with the occurrence of ACLF. Notably, in CHB patients who developed HCC, serum FGF21 exhibited a dramatic increase, which may provide important information on monitoring tumorigenesis in CHB patients. In conclusion, we revealed the diverse changes of circulating FGF21 in HBV-related diseases. FGF21 may be a useful biomarker in monitoring the tumorigenesis in patients with CHB.